X-teams: why they succeed and how to nurture them - Ancona, Deborah (Henry Stewart Talks, 2023)
X-teams, Teamwork, Culling ideas, Funding, Management and evaluation, Hierarchy, Innovation, Cultural differences, Organizational culture, Internal model